Optimisation of Geometric Parameters of Gears under Variable Loading Condition - Bozca, Mehmet; Dikmen, Ferhat (TRANS TECH PUBLICATIONS LTD, 2012)
Optimisation of geometric parameters of gears under variable loading condition is studied. Bending stress is considered as objective function and contact stress is considered as constraint function. Bending stress and contact stress are calculated depending on zero tooth modification, positive tooth modification and negative tooth modification by using developed MATLAB program respectively. Obtained results are compared and presented graphically. It is concluded that tooth modification is effective parameter for optimisation of geometric parameters of gears under variable loading condition. By optimising the geometric parameters of the gears, such as, the module, number of teeth, helix angle, and face width, it is possible to obtain a light-weight-gears structures. All optimised geometric design parameters also satisfy all constraints.
Keywords: Gears; tooth modification; bending stress; contact stress; Engineering; Materials Science